Analisis Perbandingan Tarif Rumah Sakit dan Tarif INA CBG Pada Pelayanan Rawat Inap di RS PKU Muhammadiyah Yogyakarta - Fathah, Rigel Nurul; Safitri, Teti Anggita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the difference in the actual cost or tariff of the hospital with the Indonesian Case-Based Group (INA-CBG) tariff on the payment claims of inpatients participating in the National Health Insurance (JKN) and the factors causing the difference and the difference in rates. The research was conducted at PKU Muhammadiyah Hospital Yogyakarta.This study uses descriptive methods to collect primary and secondary data in the form of observations, interviews, and the collection of hospital financial data. The data analysis technique in this research is descriptive and oriented to the actual cost of BPJS claims for JKN participants in class 3 health services at PKU Muhammadiyah Hospital Yogyakarta. From the results of the study, hospital rates showed a difference from INA CBG rates. Of the 372 diseases, there was a positive difference between surgeons, neurologists, obstetricians, and pediatricians, while for internal medicine specialists, the hospital experienced a negative difference (loss). The factors causing the difference in real hospital rates and INA CBG package rates in class 3 inpatient services at PKU Muhammadiyah Yogyakarta Hospital are 1. Determination of real tariff standards with INA CBG package rates by the hospital (2) Accuracy in coding diagnosis This study aims to analyze the difference in the actual cost or tariff of the hospital with the Indonesian Case-Based Group (INA-CBG) tariff on the payment claims of inpatients participating in the National Health Insurance (JKN) and the factors causing the difference and the difference in rates. The research was conducted at PKU Muhammadiyah Hospital Yogyakarta. This study uses descriptive methods to collect primary and secondary data in the form of observations, interviews, and the collection of hospital financial data. The data analysis technique in this research is descriptive and oriented to the actual cost of BPJS claims for JKN participants in class 3 health services at PKU Muhammadiyah Hospital Yogyakarta. From the results of the study, hospital rates showed a difference from INA CBG rates. Of the 372 diseases, there was a positive difference between surgeons, neurologists, obstetricians, and pediatricians, while for internal medicine specialists, the hospital experienced a negative difference (loss). The factors causing the difference in real hospital rates and INA CBG package rates in class 3 inpatient services at PKU Muhammadiyah Yogyakarta Hospital are 1. Determination of real tariff standards with INA CBG package rates by the hospital (2) Accuracy in coding diagnosis